2023
DOI: 10.1371/journal.pone.0283651
|View full text |Cite
|
Sign up to set email alerts
|

Costs of inpatient care and out-of-pocket payments for COVID-19 patients: A systematic review

Kamal Gholipour,
Sama Behpaie,
Shabnam Iezadi
et al.

Abstract: Objective To identify the costs of hospital care for patients with COVID-19 and the amount of out-of-pocket payments. Methods We conducted a systematic review using Scopus and WEB OF SCIENCE and PubMed databases in April 5, 2022 and then updated in January 15, 2023. English articles with no publication year restrictions were included with study designs of cost-of-illness (COI) studies, cost analyses, and observational reports (cross-sectional studies and prospective and retrospective cohorts) that calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
(75 reference statements)
0
4
1
Order By: Relevance
“…When comparing the retrospective resource utilisation study conducted by Alvis-Zakzuk et al 18 with our own findings regarding resource utilisation, Alvis-Zakzuk et al 18 reported a total cost per patient of US$6552, 20 which is lower than our mean of US$15 001. This suggests that their study likely included a population with a more moderate disease, considering the initial differences in sociodemographic variables.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…When comparing the retrospective resource utilisation study conducted by Alvis-Zakzuk et al 18 with our own findings regarding resource utilisation, Alvis-Zakzuk et al 18 reported a total cost per patient of US$6552, 20 which is lower than our mean of US$15 001. This suggests that their study likely included a population with a more moderate disease, considering the initial differences in sociodemographic variables.…”
Section: Discussioncontrasting
confidence: 46%
“…LOS was identified as the primary driver of resource utilisation in both studies ( table 5 ). Gholipour et al ’s 20 systematic review indicates that the average cost of hospitalisation, categorised based on ICU hospitalisation and hospitalisation inwards, was US$18 741, which provides valuable context for our own findings with a mean cost of US$15 001.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The costs associated with treating infected patients put significant pressure on health systems, especially in regions with limited resources [10]. Infected patients may require a diverse range of medical resources, from hospitalization in wards and ITUs to specialized interventions [11,12].…”
Section: Of 29mentioning
confidence: 99%
“…Due to the complexity of treating COVID-19 patients, especially in intensive care units, hospitalization costs have increased worldwide. A systematic review found that in Germany, the total cost of hospitalization in intensive care per patient was USD 100,789 [5]. Even though the world was neither prepared nor coordinated for such an emergency, there was an impressive mobilization of human societies worldwide.…”
Section: Introductionmentioning
confidence: 99%